Ankylosing spondylitis: acute/subacute vs. chronic iridocyclitis - a bidirectional two-sample Mendelian randomization study - Li, Hui; Xu, Yingying; Guo, Qin; Zhang, Tiantian; Zhou, Shufen; Wu, Meimei; Cheng, Yuanxiong; Guo, Chengshan (Frontiers in Immunology, 2024)
Background Observational studies found associations between ankylosing spondylitis (AS) and iridocyclitis (IC), but the causality remained unconfirmed. Methods We employed two-sample Mendelian randomization (MR) to investigate the bidirectional causal relationships between AS and IC. Single-nucleotide polymorphisms (SNPs) were chosen from the FinnGen database’s genome-wide association studies (GWAS) following a rigorous evaluation of the studies’ quality. Sensitivity analysis was performed to assess the potential influence of pleiotropy and heterogeneity on the MR findings. Results Elevated genetic risk for AS showed positive causal effects on IC and its subtypes (IC, OR = 1.094, 95% CI = 1.035-1.157, P = 0.00156; Acute/Subacute IC, OR = 1.327, 95% CI = 1.266-1.392, P = 8.73×10-32; Chronic IC, OR = 1.454, 95% CI = 1.308-1.618, P = 5.19×10-12). Significant causal association was specifically observed between Acute/Subacute IC and AS (OR = 1.944, 95% CI = 1.316-2.873, P = 8.38×10-4). Sensitivity analysis suggested that horizontal pleiotropy was unlikely to influence the causality, and the leave-one-out analysis confirmed that a single SNP did not drive the observed associations. Conclusion Our findings provide new proof of a positive causal relationship between AS and IC in the European population. Notably, it is Acute/Subacute IC, rather than IC as a whole or Chronic IC, that is associated with an elevated risk of AS. These results emphasize the significance of considering AS characteristics in the diagnosis of Acute/Subacute IC.